2021
DOI: 10.3390/e23060753
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Heart Rhythm Complexity in Identifying High-Risk Pulmonary Hypertension Patients

Abstract: Pulmonary hypertension (PH) is a fatal disease—even with state-of-the-art medical treatment. Non-invasive clinical tools for risk stratification are still lacking. The aim of this study was to investigate the clinical utility of heart rhythm complexity in risk stratification for PH patients. We prospectively enrolled 54 PH patients, including 20 high-risk patients (group A; defined as WHO functional class IV or class III with severely compromised hemodynamics), and 34 low-risk patients (group B). Both linear a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…The MSE complexity measure analysis method was proposed by Costa et al (2002) , which quantifies the non-linear dynamics of complex systems on multiple scales based on SampEn and measures signal complexity more comprehensively. Several studies have been conducted to apply the complexity indicators quantified by this method for disease prediction, classification and prognostic assessment ( Lin et al, 2016 ; Frassineti et al, 2021 ; Tang et al, 2021 ; Yang et al, 2021 ; Liao et al, 2022 ). For example, Frassineti et al (2021) found that MSE analysis had prescreening value in neonatal seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSE complexity measure analysis method was proposed by Costa et al (2002) , which quantifies the non-linear dynamics of complex systems on multiple scales based on SampEn and measures signal complexity more comprehensively. Several studies have been conducted to apply the complexity indicators quantified by this method for disease prediction, classification and prognostic assessment ( Lin et al, 2016 ; Frassineti et al, 2021 ; Tang et al, 2021 ; Yang et al, 2021 ; Liao et al, 2022 ). For example, Frassineti et al (2021) found that MSE analysis had prescreening value in neonatal seizures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Frassineti et al (2021) found that MSE analysis had prescreening value in neonatal seizures. Tang et al (2021) showed that MSE analysis was helpful for the identification of high-risk pulmonary hypertension patients. In contrast to other single time scale analyses, MSE can reflect an understanding of a range of time scales ( Busa and van Emmerik, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MSE method employs an entropy measure to quantify the degree of unpredictability of RR time series, taking into account the complex temporal fluctuations conveyed in different scales. Even though studies that have analysed the nonlinear dynamics and the complexity of HRV using long-term RR time series in MetS are scarce, the decrease in maximum MSE indicates higher predictability of cardiac fluctuations and lower randomness and complexity in cardiac activity [71], which has been described in other populations such as heart failure, high-risk pulmonary hypertension and peritoneal dialysis patients [62,63,72].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we studied the nonlinear dynamics of the RR time series. Although the use of nonlinear parameters for HRV analysis is not widely implemented, these measures have been shown to be useful for the assessment of cardiovascular risk and sudden cardiac death [28,[59][60][61][62] and are a wellrecognized way to distinguish between physiological and pathological conditions [58]. Furthermore, the importance and pathophysiological significance of the DFA scaling exponents and the multiscale properties, as well as their advantages over traditional HRV measurements, have been highlighted by some [63,64], even though the precise mechanisms underlying their modifications are not completely understood.…”
Section: Nonlinear Analysesmentioning
confidence: 99%
See 1 more Smart Citation